Pengaruh Perbandingan Tepung Beras dengan Tepung Pisang (Musa paradisiaca L.) Terhadap Karakteristik Kue Apem Kukus - Purnamasari Nababan, Joice Pratiwi; Indri Hapsari Arihantana, Ni Made; Diah Puspawati, Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i03.p20, 2023)
This study was aimed to determine the effect comparison of rice flour with banana flour on the characteristics of steamed apem cake and determine the best comparison of rice flour and banana flour to produce steamed apem cake with the best characteristics. The experiment used a completely Randomized Design with comparison of rice flour and banana flour treatment consisting of 6 levels: 100%: 0%, 90%: 10%, 80%: 20%, 70%: 30%, 60%: 40%, and 50%:50%. The treatment was repeated 3 times to obtain 18 experimental units. The data was analyzed by using analysis of variance and if the treatment had a significant effect, then followed by a Duncan Multiple Range Test (DMRT). The results showed that the comparison of rice flour with banana flour had a significant effect (P<0,05) on water content, ash content, protein content, fat content, crude fiber content, texture and overall acceptability (hedonic), aroma, taste, texture, and color (scoring). Steamed apem cake produced from the comparison of 80% rice flour and 20% banana flour had the best characteristics, with water content of 36.43%, ash content of 0.57%, protein content of 2.90%, fat content of 1.72%, carbohydrate content of 58.38%, crude fiber content of 2.45% and swelling power of 32.17%, whitish brown color, very soft texture, and very sweet taste was liked, the characteristic aroma of bananas and overall acceptance was very liked.